Ethnopharmacological evaluation of Cenchrus ciliaris for multiple gastrointestinal disorders - Aleem, Ambreen; Janbaz, Khalid Hussain (Bangladesh Journal of Pharmacology, 2017)
This study was conducted to rationalize the traditional uses of Cenchrus ciliaris in gastrointestinal disorders using in vivo and ex vivo assays. The antidiarrheal effect was evaluated in rats by the castor oil-induced diarrheal model. C. ciliaris (100, 300 and 500 mg/kg) reduced the castor oil-induced diarrhea significantly. Another study carried out in mice to determine the intestinal transit rate showed that C. ciliaris (100 and 200 mg/kg) inhibited the transit rate significantly. Ex vivo assay demonstrated that C. ciliaris (0.011 mg/mL) relaxed the spontaneous and K+ (80 mM)-induced contractions, like verapamil. The crude extract (75, 100 and 150 mg/kg) also exhibited significant anti-emetic activity in chicks. These results indicate the presence of antispasmodic, antidiarrheal and antiemetic activities in C. ciliaris, thus providing the scientific basis for its traditional uses. Video Clip of Methodology: 56 sec Full Screen Alternate